2016
DOI: 10.1016/j.enconman.2016.03.070
|View full text |Cite
|
Sign up to set email alerts
|

On the economics of stand-alone renewable hybrid power plants in remote regions

Abstract: In recent years ever more examples of regions that have managed to achieve or orientate themselves towards renewable energy sufficiency are emerging. However, actions to create energy autonomy are mainly the result of isolated activities and they are less driven from fully organized movements. In addition, total energy independence without the support of a centralized electrical grid is yet to be achieved. The objectives of this work are to investigate the associated costs of stand-alone renewable hybrid power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…It has been shown that renewable-based projects are more likely to be economically viable in remote regions [2]. Public awareness and acceptance is a very important factor when the implementation of new policies is required in a society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that renewable-based projects are more likely to be economically viable in remote regions [2]. Public awareness and acceptance is a very important factor when the implementation of new policies is required in a society.…”
Section: Introductionmentioning
confidence: 99%
“…However, energy autonomy exclusively based on renewable energy sources (RES) is a developing idea that can result in a number of benefits [1]. Apart from boosting the local, and as a consequence the national, economy by creating jobs and increasing the penetration of RES in the national portfolio, renewable-based energy autonomy can decrease the environmental impact and economic expenditure of energy generation in remote regions [2,3]. Envisioned energy strategies must be based on social, political, environmental and economic considerations [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, their relatively high costs and intermittent operation makes their applications more demanding and complex. Regions without easy access to fossil fuels due to their remote location or costly conversion processes can constitute good application cases for renewable systems (Petrakopoulou, 2016). This study examines the case study of Skyros, a non-interconnected island in the Aegean Sea in Greece (Petrakopoulou, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, several studies have investigated the possibility of constructing small stand-alone electrical grids, powered only by renewable energy sources [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In other interesting study, Petrakopoulou [10] simulated a hybrid power plant to satisfy the electrical demand of Skyros, a small Greek island, located in the middle of Aegean Sea. The system proposed is composed by solar thermal and photovoltaic, hydroelectric generators and wind turbines.…”
Section: Introductionmentioning
confidence: 99%